An investigation of the affective experience of females at high risk for eating disorders in general and pathology-specific contexts. (1st October 2019) - Koushiou, Maria; Merwin, Rhonda M.; Anderson, Drew; Karekla, Maria
Abstract: Objective: Difficulties with emotional experiences have long been implicated in the development or maintenance of eating disorders (EDs). However, the vast majority of this work is theoretical or self-report, with few studies examining the somatic-affective experience of individuals with EDs under experimental conditions. The aim of the current study was to: i) examine physiological reactivity and subjective report of emotional experiences in response to ED pathology-specific and general affective film clips, and ii) examine the impact of film on body size estimation in females at risk for EDs. Method: Females aged 14–24 years old of either high (N = 42) or low (N = 43) risk for EDs viewed pathology-specific and general affective film clips and provided their affective ratings and body-size estimations post film clips. Heart Rate and Skin Conductance Levels were recorded during each clip. Results: High risk participants evidenced greater physiological arousal across conditions and in both general and pathology-specific affective contexts. Negative affect induced via the ED-pathology specific film clip had a greater impact on the high risk group's body-size estimations. Conclusions: Individuals at risk for EDs seem to experience greater physiological arousal and this may influence the experience of their bodies, or direct attention to their body as a way to attenuate unwanted emotion or due to somatic feedback.